2008
DOI: 10.1007/s00383-008-2313-7
|View full text |Cite
|
Sign up to set email alerts
|

Dismembered pyeloplasty using double ‘J’ stent in infants and children

Abstract: We recommend double 'J' stent as the safest mode of drainage in pyeloplasty in infants and children. Keeping a double-J stent across the anastomosis reduces the complications and the hospital stay in these patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
31
0
7

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(39 citation statements)
references
References 10 publications
1
31
0
7
Order By: Relevance
“…[6] Using JJ catheter during pyeloplasty eliminates the need for external drainage. [2,3,5,7] Ninan et al [8] performed 61 dismembered pyeloplasties in 60 consecutive patients with UPJ obstruction. In 58 patients, JJ catheter was placed in an antegrade fashion during the operation, so they recommended JJ stenting as the safest mode of drainage in pyeloplasty in infants and children.…”
Section: Discussionmentioning
confidence: 99%
“…[6] Using JJ catheter during pyeloplasty eliminates the need for external drainage. [2,3,5,7] Ninan et al [8] performed 61 dismembered pyeloplasties in 60 consecutive patients with UPJ obstruction. In 58 patients, JJ catheter was placed in an antegrade fashion during the operation, so they recommended JJ stenting as the safest mode of drainage in pyeloplasty in infants and children.…”
Section: Discussionmentioning
confidence: 99%
“…[16] Ninan et al, reported a review of the records of 60 patients who underwent pyeloplasty in 2008. [11] They strongly recommended double 'J' stenting, claiming that it was the safest mode of drainage in paediatric pyeloplasty. The disadvantages of the double 'J' stent include that it can cause stentrelated complications such as urinary tract infection and provoke obstruction of the ureter by irritating the mucosa of the ureter or the renal pelvis.…”
Section: Discussionmentioning
confidence: 99%
“…[17,18] Several favourable reports on the use of internal stents have been published in recent years showing their several advantages. [11,19] The advantages of a double 'J' stent compared with a nephrostomy tube include a shorter hospital stay and a lower morbidity rate. [20,21] Furthermore, double 'J' stents prevent adhesion to the suture site by splinting the suture line, help to maintain an appropriate diameter and alignment of the ureter, and limit ureter kinking.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Once an approach is chosen, the surgeon must then decide whether to place a ureteral stent for internal urinary drainage, to select an external stent such as a trans-nephrostomy tube or trans-pyelostomic stent, or to just simply leave a perinephric drain without urinary diversion. Nevertheless, whether a temporary urinary stent such as a nephrostomy tube or ureteric stent leads to better results than simple perinephric drainage during the hospital stay remains controversial [6-11]. Nowadays, many surgeons tend to prefer internal drainage to external drainage [12,13].…”
Section: Introductionmentioning
confidence: 99%